Continuous improvement of fitness‐for‐duty management programs for workers engaging in stabilizing and decommissioning work at the Fukushima Daiichi Nuclear Power Plant. Issue 2 (27th March 2018) - Mori, Koji; Tateishi, Seiichiro; Kubo, Tatsuhiko; Kobayashi, Yuichi; Hiraoka, Ko; Kawashita, Futoshi; Hayashi, Takeshi; Kiyomoto, Yoshifumi; Kobashi, Masaki; Fukai, Kota; Tahara, Hiroyuki; Okazaki, Ryuji; et al.
Abstract : Background: Numerous workers have participated in recovery efforts following the accident that occurred at the Tokyo Electric Power Company (TEPCO) Fukushima Daiichi Nuclear Power Plant after the Great East Japan Earthquake. These workers, belonging to various companies, have been engaged in various tasks since the accident. Given the hazards and stress involved in these tasks and the relatively long time required to transport sick or injured workers to medical institutions, it became necessary to quickly implement a more stringent management program for fitness for duty than in ordinary work environments. Case: It took considerable time to introduce and improve a fitness‐for‐duty program because of several concerns. Various efforts were conducted, sometimes triggered by guidance from the Ministry of Health, Labour and Welfare (MHLW), but the implementation of the program was insufficient. In April 2016, a new program was initiated in which all primary contractors confirmed that their subcontractors had achieved five conditions for workers' fitness for duty on the basis of guidance from the MHLW and occupational health experts. TEPCO confirmed that all primary contractors had implemented the program successfully as of the end of November 2016. Conclusion: Following a disaster, even though the parties concerned understand the necessity of fitness‐for‐duty programs and that companies in high positions have responsibilities beyond their legal requirements, it is highly possible that they may hesitate to introduce such programs without guidance from the government. It is necessary to prepare a governmental framework and professional resources that introduce these stringent management programs quickly.